Kesan teknik permanian beradas terhadap kadar kesuburan telur, kadar penetasan telur dan kadar kematian awal embrio - Mohamad Aryanto Jumat (Universiti Malaysia Sabah, 2017)
This study aimed to determine the rate of fertilization and hatching rate of eggs laid by hens and rate of early embryo death through two methods of artificial insemination. A total of 10 roosters of Sandakan were used in this study as well as 30 hens were divided into two groups with each group containing 15 hens. Cock semen were collected before hens fertilized artificial insemination process. Once hens fertilized, eggs produce should be collected and incubated. Egg incubation process took21 days before the eggs hatch. Candling were done on the seventh day of incubation to determine the rate of egg fertilization. Two methods of Artificial Insemination were used to determine the rate of fertilization, rate of hatchability and rate of the early death of embryo. The method were using drop method of sperm on the cloaca and 2cm penetration of the sperm into the cloaca. 2cm penetration of the sperm into the cloacae gave a better result ( p<0.05 ) than drop method. This is because injection of sperm to penetrate 2cm depth into the cloaca enables the sperm to deposit near the storage tubule.